2008
DOI: 10.4049/jimmunol.180.6.3689
|View full text |Cite
|
Sign up to set email alerts
|

Non-T Cell Activation Linker Promotes Mast Cell Survival by Dampening the Recruitment of SHIP1 by Linker for Activation of T Cells

Abstract: The linker for activation of T cells (LAT) and the non-T cell activation linker (NTAL) are two transmembrane adapters which organize IgE receptor (FcεRI) signaling complexes in mast cells. LAT positively regulates, whereas NTAL negatively regulates mast cell activation. We previously found that the four distal tyrosines of LAT can generate negative signals. We show here that two of these tyrosines provide two binding sites for SHIP1, that LAT recruits SHIP1 in vivo, and that SHIP1 recruitment is enhanced in NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 55 publications
3
26
0
1
Order By: Relevance
“…LAT2 is a wellknown antagonist of LAT1 in mouse mast cells, and LAT2-deficient mice exhibited enhanced secretory responses on FcRI engagement (42). The exact mechanisms by which LAT2 inhibits mast cell activation is, however, largely unknown (22), and it has been reported to interact with six proteins only. Dok-3, a cytosolic adapter of the Dok family is also associated with negative regulation and was inducibly recruited in the SLP76 interactome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAT2 is a wellknown antagonist of LAT1 in mouse mast cells, and LAT2-deficient mice exhibited enhanced secretory responses on FcRI engagement (42). The exact mechanisms by which LAT2 inhibits mast cell activation is, however, largely unknown (22), and it has been reported to interact with six proteins only. Dok-3, a cytosolic adapter of the Dok family is also associated with negative regulation and was inducibly recruited in the SLP76 interactome.…”
Section: Discussionmentioning
confidence: 99%
“…LAT2 is absent in resting T cells, but present in B cells where it fulfills some of the functions exerted by LAT1 in T cells. In mast cells, LAT1 and LAT2 function as a pair of antagonistic molecules (22). The role of SLP76 in mast cells cannot therefore be deduced from that of SLP76 in T cells, and the mechanism(s) by which it contributes to mast cell activation needs to be established.…”
mentioning
confidence: 99%
“…In mast cells, it was reported that SHIP1 is recruited by LAT following FcεRI engagement (5) and that it negatively regulates FcεRI signaling by controlling the levels of PI3,4,5P 3 and, independently of its phosphatase activity, by antagonizing Grb2 and p52Shc signaling to Ras/MAPK (5, 36), as well as by recruiting Dok-1 and RasGAP (37,38). Although SHIP1 becomes tyrosine phosphorylated in response to FcεRI stimulation, its phosphatase activity does not seem to be regulated by phosphorylation but rather by its localization at the plasma membrane (35).…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-induced LAT phosphorylation results in the recruitment of signaling mediators, such as PLCg, Gads/SLP-76/Vav, and Grb/Shc/Sos, leading to degranulation, as well as to cytokine and eicosanoid production (4). Moreover, LAT is responsible for recruitment of the lipid phosphatase SHIP1, the major negative regulator of FcεRI signaling (5). Consistent with a view of adapters as key players in coordinating FcεRI signaling, mice lacking LAT (6), non-T cell activation linker (7), SLP-76 (8), or Gab2 (9) are resistant to IgEmediated passive anaphylaxis.…”
mentioning
confidence: 99%
See 1 more Smart Citation